Philosophy of Birth: Approach from the Embodied and Intersubjective Phenomenology of Merleau-Ponty - Videla Reyes, Ronnie; Cortez Burotto, Marco (Resonancias. Revista de Filosofía, 2019)
The present study approaches birth as a philosophical problem from an intersubjective and embodied perspective derived from the analysis of the Body and the Other present in the Phenomenology of Perception of Merleau-Ponty. Based on the foregoing, the limitations of the Being-with-the-other (Mitdasein) of Heidegger and the Otherness of Levinas framed in the relationship of the face in its attempt to approach a philosophy of birth from an approximation of shared world (mother-father-son). In addition, there is a need to incorporate the three stages of pregnancy into the philosophical problem: pregnancy-birth-puerperium, since these are fundamental to illustrate in a profound way the relational and embodied dimension of this process that exhibits temporality and historicity.